Seeking a Balance: Helping Pre-Service Teachers Develop Positive Attitudes Towards Mathematics as they Develop Competency - Hurst, Chris; Cooke, Audrey (Australian Association for Research in Education (AARE), 2012)
Mathematical competence of teachers continues to be an issue of great interest to mathematics educators within tertiary institutions and it is often thought of simultaneously with the notion of mathematics anxiety. While there has been considerable recent research into the latter, no clear conclusions have been able to be drawn about many aspects of the phenomenon and how it is linked to mathematical competence. Most recently, international studies have highlighted notable differences in the standards of teacher preparation in different countries and in Australia new standards for accreditation of teacher education programs have been drafted. This paper reports on a part of on-going research into mathematics anxiety and competence of pre-service teachers. It uses two small samples of pre-service teachers from different cohorts of a Bachelor of Education course and attempts to identify factors that may help develop positive attitudes towards mathematics as they seek to develop their competency in mathematics. In addition, as a response to greater reported levels of anxiety regarding cognitive and knowledge traits, the paper identifies targeted professional learning and social constructivist teaching as key factors as well as the need to identify personal knowledge of mathematics as a prelude to seeking to become more competent.